2019
DOI: 10.1083/jcb.201811090
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleosome imaging reveals loose genome chromatin networks via active RNA polymerase II

Abstract: Although chromatin organization and dynamics play a critical role in gene transcription, how they interplay remains unclear. To approach this issue, we investigated genome-wide chromatin behavior under various transcriptional conditions in living human cells using single-nucleosome imaging. While transcription by RNA polymerase II (RNAPII) is generally thought to need more open and dynamic chromatin, surprisingly, we found that active RNAPII globally constrains chromatin movements. RNAPII inhibition or its rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
285
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(323 citation statements)
references
References 101 publications
(192 reference statements)
36
285
2
Order By: Relevance
“…In quiescent cells, the share of quickly diffusing RNA Pol II complexes was reduced compared to actively transcribing cells and, upon elongation inhibition using 5,6-Dichloro-1-β-D-ribofuranosylbenzimidazole (DRB), the slowly diffusing fraction was greater than in untreated cells, indicating tenacious immobilization of RNA Pol II on the DNA template after initiation ( Figure 4c). The average diffusion constants in serum starved and DRB treated cells are similar for the three populations, suggesting that RNA Pol II not phosphorylated in absence of serum coherent with published data identifying serum starved cells in the first place [25]. We then compared the effect of transcriptional activity on chromatin dynamics in serum-starved and -stimulated cells.…”
Section: Transcription Status Modulates Chromatin Diffusion Processessupporting
confidence: 77%
See 1 more Smart Citation
“…In quiescent cells, the share of quickly diffusing RNA Pol II complexes was reduced compared to actively transcribing cells and, upon elongation inhibition using 5,6-Dichloro-1-β-D-ribofuranosylbenzimidazole (DRB), the slowly diffusing fraction was greater than in untreated cells, indicating tenacious immobilization of RNA Pol II on the DNA template after initiation ( Figure 4c). The average diffusion constants in serum starved and DRB treated cells are similar for the three populations, suggesting that RNA Pol II not phosphorylated in absence of serum coherent with published data identifying serum starved cells in the first place [25]. We then compared the effect of transcriptional activity on chromatin dynamics in serum-starved and -stimulated cells.…”
Section: Transcription Status Modulates Chromatin Diffusion Processessupporting
confidence: 77%
“…adding serum to the medium brings cells back into the cell cycle and stimulates transcriptional activity [20,24,25]. Diffusion constants were calculated for each pixel based on the model selected by Bayesian inference.…”
Section: Single-cell Biophysical Property Maps Of Genome Conformationmentioning
confidence: 99%
“…For example, G0 B cells and mitotic yeast cells have more compact chromatin than proliferating and interphase cells, respectively, but they also have lower short-range Hi-C contact probabilities 56,57 . Time-resolved single-nucleosome tracking of RPE-1 cells has also shown that G0 phase chromatin is more dynamic than proliferating cell chromatin 58 . These counter-intuitive observations reflect our incomplete understanding of the many factors that influence chromatin structure and function in situ 59 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, their mobility is modulated by attractive interactions with other loci by factors that themselves are dynamic, and by local chromatin density. Live cell imaging experiments have examined locus motion extensively and found differences in mobility and constrained diffusion dependent on sub-nuclear position and chromatin state and activity (Bronshtein et al, 2009;Bronshtein et al, 2015;Hediger et al, 2002;Marshall et al, 1997;Nagashima et al, 2019;Shinkai et al, 2016;Thakar et al, 2006;Therizols et al, 2010). In such experiments the movement detected is strongly constrained by the fact that loci are part of very long chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…heterochromatic loci and loci tethered to the nuclear periphery vs. loci located in the nuclear interior (Bronshtein et al, 2009;Bronshtein et al, 2015;Hediger et al, 2002;Marshall et al, 1997;Nagashima et al, 2019;Shinkai et al, 2016;Thakar et al, 2006;Therizols et al, 2010).…”
Section: Introductionmentioning
confidence: 99%